Renda básica como instrumento de liberdade - Silva, Jônatas Rodrigues da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
A presente tese conceitua e discorre sobre Renda Básica incondicional como um instrumento de liberdade e segurança protetora. O trabalho estabelece uma correlação entre pobreza e ausência de liberdade. Ele também explicita a desigualdade histórica e inercial da concentração de renda brasileira, caracterizando a pobreza como o principal empecilho à liberdade. Ainda esta tese joga luz na forte concentração de renda e riqueza no Brasil como um problema social que precisa ser melhor entendido.

This thesis conceptualizes and discusses unconditional basic income as an instrument of freedom and protective security. The work establishes a correlation between poverty and the absence of freedom. It also explains the inequality historical and inertial of Brazilian income concentration, characterizing poverty as the main obstacle to freedom. This thesis still gives emphasis on the high concentration of income and wealth in Brazil as a social problem that needs to be better understood.
Basic income as a instrument of freedom
Keywords: Renda Básica; Desigualdade; Liberdade; Pobreza; Basic Income; Inequality; Freedom; Poverty